ASSESSMENT OF VIRAL CONTENT IN NEWCASTLE DISEASE VACCINE OBTAINED FROM TWO DIFFERENT POULTRY SHOPS USING PRIMARY CHICKEN FIBROBLAST CELL CULTURE - Kencana, Gusti Ayu Yuniati (Buletin Veteriner Udayana, 2013)
Newcastle Disease (ND) is still endemic in Indonesia, characterized by its your-round occurrence. Many measures have been adopted by the government to prevent the spread of the disease including vaccination using both active and inactive vaccine. The quality of vaccine is influenced by its viral content which determines the success of ND vaccination in chicken flock. The viral content in ND vaccine can be determined by measuring its eggs lethal dose-50 (ELD 50 ) or Tissue Culture Infective Dose-50 (TCID 50 ) and the minimum viral content considered to be appropriate for active ND vaccine is 6 6,5 /single dose. This study was conducted to find out the viral content of ND vaccine marketed in some poultry shops. ND vaccine of  LaSota strain were obtained from 2 different poultry shops and the viral content was determined in Chicken embryo fibroblast (CEF). The vaccines were reconstituted vaccine diluent and diluted serially in 10-fold diluted. Each dilution was inoculated into 4 wells of confluent CEF cultured in 96 well microplate. The TCID 50 was then calculated by Reed and Muench method. The TCID 50 of each vaccine was determined 4 times (4 replications). The result showed that the titer of the virus in the vaccine were 6 6,7 and 6 7 TCID50/per dose which mean that both vaccines were still above the minimum standard of viral content recommended by some workers.
Keywords: ND vaccine, TCID50, CEF.